PENGARUH KEPEMIMPINAN TRANFORMASIONAL DAN TRANSAKSIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU SMK â€œMâ€ PEKANBAR - Yapentra, Arhipen; Herman, Herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
The research objective was to analyze the effect of Â tranformational and transactional leadership towards Organizational Citizenship Behavior (OCB) of Teachers of Â SMK